HERMENEUTIKA MUHAMMAD SYAHRUR ( KATA NISA’ DALAM QS. ALI IMRAN:14 ): (KAJIAN HERMENEUTIKA MUHAMMAD SYAHRUR) - Dwi Elok Fardah; Maula Sari (Tanzil: Jurnal Studi Al-Quran, 2022)
One of the Islamic religious thinkers who has contributed to the contemporary era is Muhammad Syahrur. Syahrur argues that in understanding the verse, it is not always fixed on traditional interpretation. On Q.S Āli ‘Imrān [3]: 14 in interpreting the word nisā’ which according to him, the word if it is interpreted as "adult woman" is not appropriate at this time. This study uses a library research approach and uses a semantic method. Syahrur also uses the term lā tarādduf theory, namely the anti-synonymity theory in which the theory is that one word has several meanings according to the context of the verse. Syahrur pointed out that the position of women is equal to that of men, so that women are not considered as objects of oppression and are equalized with objects.